Effects of benidipine, paracetamol, and their combination on postoperative and normal tissue pain thresholds - Bedir, Zehra; Ozkaloglu Erdem, Kezban Tuna; Doymus, Omer; Suleyman, Halis; Yavuzer, Bulent; Cicek, Betul; Altuner, Durdu; Mammadov, Renad; Yilmaz, Mehmet; Coban, Taha Abdulkadir; Suleyman, Bahadir; Bulut, Seval (Frontiers in Pharmacology, 2024)
In clinical practice, inadequate pain inhibition leads to increased morbidity and mortality. Increased intracellular calcium, oxidants, and proinflammatory cytokines are known to play a role in the pathogenesis of postoperative pain. Therefore, we investigated the analgesic effects of benidipine, paracetamol, and benidipine-paracetamol combination (BPC) on postoperative and normal pain thresholds in rats.Material and methods: Sixty-four male albino Wistar rats weighing 285-295 g were used.The without-incision rats were divided into 4 subgroups: healthy control, benidipine alone, paracetamol alone, and BPC. The scalpel-incision rats were divided into 4 subgroups: scalpel incision, scalpel incision+benidipine, scalpel incision+paracetamol, and scalpel incision+BPC. Paw pain thresholds of rats were measured using a Basile algesimeter.Biochemical analyses were performed on the paw tissues of 6 rats randomly taken from the experimental groups, each containing 8 rats. Rats were sacrificed immediately after the measurements. After the pain threshold tests were finished, the paw tissues were removed and malondialdehyde (MDA), total glutathione (tGSH), cyclooxygenase (COX), and interleukin-6 (IL-6) levels were measured.Results: There was no significant difference between the groups in paw pain threshold and measured biochemical parameters in rats without incision. The decrease in the pain threshold of the incised paw was also best prevented by BPC, followed by benidipine and then paracetamol. Furthermore, increases in scalpel-incised paw tissue MDA, COX-2, and IL-6 levels and the decrease in tGSH were significantly suppressed by benidipine and BPC, while paracetamol could only significantly inhibit the increase in IL-6 production.The combination of the L-type Ca 2+ channel blocker benidipine and paracetamol (BPC) may provide potent analgesia. Our experimental results support that BPC may be useful in the treatment of severe pain that cannot be adequately inhibited by paracetamol.